Structure of Intestinal and Kidney Tissue of Carp (Cyprinus carpio) Maintained in Salinity Media and Feed Enriched with Guava Leaf Flour (Psidium guava) - Pulungan, Amar Doli; Windarti, Windarti; Eddiwan, Eddiwan; Effendi, Irwan; Kurniawan, Ronal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Carp (Cyprinus carpio) is one of the freshwater fishery commodities with high economic value. Keeping carp in saline media can affect the osmoregulation system, impacting the performance of vital organs such as the intestines and kidneys. Such disturbances can potentially reduce fish's health and survival rate. One strategy that can be used to increase the fish's immune system is through feed supplementation with natural immunostimulants, one of which is guava leaf flour (Psidium guajava), which is known to contain bioactive compounds such as flavonoids, tannins, and saponins. This study aims to evaluate the effectiveness of guava leaf flour-enriched feed on the histological structure of the intestines and kidneys of carp raised in saline media and exposed to Aeromonas hydrophila bacterial infection. The study was conducted from August to October 2024 at the Biotechnology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The method used was an experiment with a completely randomized design (CRD) consisting of five guava leaf flour dosage treatments with three replicates. The results showed that the histological structure of the intestine in all treatments was relatively normal, with neatly arranged villi and round to oval goblet cells. However, in the guava leaf powder supplementation treatment, several abnormalities were found in the kidney tissue, including inflammation, hemorrhage, and necrosis. This indicates that the salinity factor has a greater effect on kidney damage than the effect of immunostimulant administration. Nevertheless, the administration of guava leaf powder still positively improved the immune response and survival rate of fish. The optimal dose was obtained in treatment P2 (15 g/kg feed) with a survival rate of 83.33–93.33%. The water quality parameters during the study were still within the acceptable range for aquaculture, namely temperature 28–31°C, DO 3.7–7.4 mg/L, and pH 5.5–7. Thus, it can be concluded that feeding fish with guava leaf flour-enriched feed is effective in maintaining intestinal histology and increasing the survival rate of carp in saline media, although it cannot completely prevent kidney damage caused by environmental factors